2023
DOI: 10.1038/s41467-023-38027-1
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial complex III deficiency drives c-MYC overexpression and illicit cell cycle entry leading to senescence and segmental progeria

Abstract: Accumulating evidence suggests mitochondria as key modulators of normal and premature aging, yet whether primary oxidative phosphorylation (OXPHOS) deficiency can cause progeroid disease remains unclear. Here, we show that mice with severe isolated respiratory complex III (CIII) deficiency display nuclear DNA damage, cell cycle arrest, aberrant mitoses, and cellular senescence in the affected organs such as liver and kidney, and a systemic phenotype resembling juvenile-onset progeroid syndromes. Mechanisticall… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 114 publications
(183 reference statements)
0
14
0
Order By: Relevance
“…Notably, the heart is presymptomatic at this age, dilating cardiomyopathy developing by postnatal day 200 (P200) ( Rajendran et al, 2019 ). We recently ( Purhonen et al, 2023 ) extended the studies on the MYC upregulation into juvenile (postanal day 21–35) Bcs1l p.S78G mice and found a staggering level of MYC induction, 30-40-fold, in the P30 liver (symptomatic) at both mRNA and protein level. In the P30 kidney (symptomatic), Myc mRNA was upregulated about 10-fold.…”
Section: Upregulation Of Myc In Oxphos Dysfunctionmentioning
confidence: 79%
See 1 more Smart Citation
“…Notably, the heart is presymptomatic at this age, dilating cardiomyopathy developing by postnatal day 200 (P200) ( Rajendran et al, 2019 ). We recently ( Purhonen et al, 2023 ) extended the studies on the MYC upregulation into juvenile (postanal day 21–35) Bcs1l p.S78G mice and found a staggering level of MYC induction, 30-40-fold, in the P30 liver (symptomatic) at both mRNA and protein level. In the P30 kidney (symptomatic), Myc mRNA was upregulated about 10-fold.…”
Section: Upregulation Of Myc In Oxphos Dysfunctionmentioning
confidence: 79%
“…In the P30 kidney (symptomatic), Myc mRNA was upregulated about 10-fold. In the skeletal muscle, which has very low CIII activity (∼25% of wild-type) but no clear myopathy ( Purhonen et al, 2020 ), Myc mRNA was upregulated more modestly, about 2-fold ( Purhonen et al, 2023 ). Interestingly, MYC was induced presymptomatically, immediately after weaning (P18-P25) in the liver and possibly also in the other tissues.…”
Section: Upregulation Of Myc In Oxphos Dysfunctionmentioning
confidence: 99%
“…It is worth noting that our integrated analysis of hepatocyte transcriptome and ASGPR + mLT-EV proteome indicated two aspects of findings: on one hand, ASGPR + mLT-EVs inherited proliferative messages and reduced metabolic cues from donor hepatocytes in liver regeneration; on the other hand, ASGPR + mLT-EVs were particularly enriched for organelle components with no significant changes of hepatocyte transcription. For the former aspect, epidermal growth factor receptor (EGFR) is well known as a crucial regulator safeguarding liver regeneration, and multiple biological enzymes in the mitochondrial respiratory electron transport chain contribute to the cell cycle and proliferative regulation of hepatocytes [35, 36]. For the latter aspect, interestingly, ER represents the major site of protein synthesis in the cell and form the endosomal secretory pathway with Golgi apparatus [37].…”
Section: Discussionmentioning
confidence: 99%
“…For example, mitochondrial oxidative phosphorylation is impaired due to deficiency of the respiratory complex-III, 201 leading to upregulation of c-MYC in an early aging disease model of mice. 201,202 However, hyperactivation of complex-I and excessive production of superoxide ions are also reported in 3T3L1 cells ectopically expressing progerin. 203 Lower mitochondrial oxidative phosphorylation in HGPS cells could also be due to decreased glycolysis.…”
Section: And Mitochondrial Proteostasis Network In Laminopathiesmentioning
confidence: 99%
“…A number of studies have reported the interplay between the nucleus and mitochondria in laminopathies, especially in premature aging (Figure 4). For example, mitochondrial oxidative phosphorylation is impaired due to deficiency of the respiratory complex‐III, 201 leading to upregulation of c‐MYC in an early aging disease model of mice 201,202 . However, hyperactivation of complex‐I and excessive production of superoxide ions are also reported in 3T3L1 cells ectopically expressing progerin 203 .…”
Section: Crosstalk Of Nuclear and Mitochondrial Proteostasis Network ...mentioning
confidence: 99%